Determinants of unmet needs for family planning in Indonesia: Secondary data analysis of the 2017 Indonesia Demographic and Health Survey - Luh Nyoman Sumiati; Dewa Nyoman Wirawan; Luh Seri Ani (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: Globally, the unmet need for family planning remains high. The proportion of unmet needs for family planning in Indonesia was found to have declined but was still higher than the set target. In the last 5 years there have been significant development in Indonesia including infrastructure, the national health insurance program and the increasing allocation of funds to all villages throughout Indonesia with a possible impact in decreasing the unmet need for family planning. This study aims to determine the factors associated with unmet needs for family planning in Indonesia. Methods: This study uses secondary data from the 2017 Indonesia Demographic and Health Survey (IDHS) that was carried out in 34 provinces in Indonesia. The number of the analyzed samples was 26,479 of the total 2017 IDHS sample of 35,681 married women/living together with their partner aged between 15-49 years. The dependent variable is the unmet need for family planning, while the independent variables consist of four core variables namely individual, household, community and programmatic variables. Data analysis was performed with a binary logistic regression to obtain the adjusted odd ratio of each factor. Results: The proportion of unmet needs in this analysis was 14.3% (95%CI: 13.9-14.7%). Factors associated with unmet needs are maternal age 25-34 years (AOR=1.17; 95%CI: 1.01-1.36), 35-44 years (AOR=1.47; 95%CI: 1.24-1.74), ≥45 years (AOR=2.20; 95%CI: 1.81-2.68), age of last child ≥10 years (AOR=1.30; 95%CI: 1.16-1.45), number of living children <2 (AOR=1.66; 95%CI: 1.49-1.85), ideal number of children >2 (AOR=1.34; 95%CI: 1.24-1.44), have >1 son (AOR=1.12; 95% CI: 1.00-1.25), husband not working (AOR=1.89; 95%CI: 1.44-2.48), lack of knowledge about family planning methods (AOR=1.42; 95%CI: 1.24-1.63), not discussing family planning with partners (AOR=1.12; 95%CI: 1.03-1.21), living in urban area (AOR=1.24; 95%CI: 1.14-1.34) and regions with TFR >2.4 (AOR=1.59; 95%CI: 1.43-1.78). Conclusion: The proportion of unmet needs in Indonesia is still high and the dominant associated factor is the age of the mother ≥45 years. In order to decrease the family planning unmet needs, the intervention programs should be targeted to groups of women who are at risk of experiencing such unmet needs.